Intermediate-term results of image-guided brachytherapy and high-technology external beam radiotherapy in cervical cancer: Chiang Mai University experience - Tharavichitkul E. (2014)
Objective To evaluate the outcomes of image-guided brachytherapy combined with 3D conformal or intensity modulated external beam radiotherapy (3D CRT/IMRT) in cervical cancer at Chiang Mai University. Methods From 2008 to 2011, forty-seven patients with locally advanced cervical cancer were enrolled in this study. All patients received high-technology (3D CRT/IMRT) whole pelvic radiotherapy with a total dose of 45-46 Gy plus image-guided High-Dose-Rate intracavitary brachytherapy 6.5-7 Gy × 4 fractions to a High-Risk Clinical Target Volume (HR-CTV) according to GEC-ESTRO recommendations. The dose parameters of the HR-CTV for bladder, rectum and sigmoid colon were recorded, as well as toxicity profiles. In addition, the endpoints for local control, disease-free, metastasis-free survival and overall survival were calculated. Results At the median follow-up time of 26 months, the local control, disease-free survival, and overall survival rates were 97.9%, 85.1%, and 93.6%, respectively. The mean dose of HR-CTV, bladder, rectum and sigmoid were 93.1, 88.2, 69.6, and 72 Gy, respectively. In terms of late toxicity, the incidence of grade 3-4 bladder and rectum morbidity was 2.1% and 2.1%, respectively. Conclusions A combination of image-guided brachytherapy and IMRT/3D CRT showed very promising results of local control, disease-free survival, metastasis-free survival and overall survival rates. It also caused a low incidence of grade 3-4 toxicity in treated study patients. © 2013 Elsevier Inc.